The impact of e-learning usage on students' achievements: a case study. (2018) - Maabreh, Khaled Saleh
E-learning, an important internet-based tool can be implemented using communication methods and storage media that support different data types. As a virtual learning environment, e-learning has emerged in the field of higher education in countries throughout the world, including Jordan, a developing country. To evaluate the effectiveness of the e-learning program implemented in Jordan, a sample study is presented in this paper to examine the students' perceptions and attitudes related to the courses offered at the Faculty of Information Technology in Zarqa University. This study aims to evaluate the students' satisfaction and measure the influence of using an e-learning system (Moodle) on their achievements. Statistical analysis showed that the use of e-learning technology had a major effect on the students' achievements.